Insect transformation with piggyBac: getting the number of injections just right. Issue 3 (30th March 2016) - Gregory, M.; Alphey, L.; Morrison, N. I.; Shimeld, S. M.
Abstract: The insertion of exogenous genetic cargo into insects using transposable elements is a powerful research tool with potential applications in meeting food security and public health challenges facing humanity. piggyBac is the transposable element most commonly utilized for insect germline transformation. The described efficiency of this process is variable in the published literature, and a comprehensive review of transformation efficiency in insects is lacking. This study compared and contrasted all available published data with a comprehensive data set provided by a biotechnology group specializing in insect transformation. Based on analysis of these data, with particular focus on the more complete observational data from the biotechnology group, we designed a decision tool to aid researchers' decision‐making when using piggyBac to transform insects by microinjection. A combination of statistical techniques was used to define appropriate summary statistics of piggyBac transformation efficiency by species and insect order. Publication bias was assessed by comparing the data sets. The bias was assessed using strategies co‐opted from the medical literature. The work culminated in building the Goldilocks decision tool, a Markov‐Chain Monte‐Carlo simulation operated via a graphical interface and providing guidance on best practice for those seeking to transform insects using piggyBac .